2011
DOI: 10.1111/j.1447-0756.2010.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental disorders and pregnancy outcomes: A clinical study in a Japanese population

Abstract: A trend towards a lower birth weight and shorter gestational age was observed in Japanese women with well-controlled mental disorders, but the effect of well-controlled mental disorders on the perinatal outcome was minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…Our data support an increasing trend in the use of SGAs to treat a variety of psychiatric disorders, with bipolar disorder and depression being reported as the two leading indications and quetiapine being the one most commonly used. We found that 76% (n=101) of women were exposed to SGAs throughout pregnancy and 72% of the assessed cohort received psychotropic drugs in polytherapy, which is in agreement with previous reports 16 19 21 22. Frye et al 23 stated that the proportion of polytherapy treatment increased from 3.3% in 1974–1979 to 44% in 1990–1995 24.…”
Section: Discussionsupporting
confidence: 91%
“…Our data support an increasing trend in the use of SGAs to treat a variety of psychiatric disorders, with bipolar disorder and depression being reported as the two leading indications and quetiapine being the one most commonly used. We found that 76% (n=101) of women were exposed to SGAs throughout pregnancy and 72% of the assessed cohort received psychotropic drugs in polytherapy, which is in agreement with previous reports 16 19 21 22. Frye et al 23 stated that the proportion of polytherapy treatment increased from 3.3% in 1974–1979 to 44% in 1990–1995 24.…”
Section: Discussionsupporting
confidence: 91%
“…35,40,45 Moreover, weight gain during pregnancy, an important factor regarding pregnancy outcome, was only documented by 2 studies. 10,24 In addition, pregnant women taking SGAs are more likely to smoke, drink alcohol, use illicit drugs, have unwanted pregnancies, and be in a lower socioeconomic class and are less likely to take prenatal vitamins, 8,10,11,16,17 all of which are factors that may cause adverse pregnancy outcomes and lead to an overestimate of risk in our analysis. Studies using more sound methodologies are needed to consider the effects of disorder, drug dosage, timing and duration during gestation, polytherapies, and other comorbidities on pregnancy outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Although the 12 included studies in this metaanalysis were of high quality, there are still limitations within the individual studies, which weaken the strength of this metaanalysis and which must be considered. First, only 2 studies attempted to adjust for the potential effects of the underlying disease, 17,24 which include schizophrenia, bipolar disorder, and depression, all of which may be associated with adverse pregnancy outcomes and neonatal complications. 32,33,[41][42][43] As discussed, this is a major methodological weakness and affects most of the research in this field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations